Akibat Hukum Akta Wasiat (Testament Acte) Yang Tidak Didaftarkan Oleh Notaris Secara Elektronik Melalui Kementerian Hukum Dan Hak Asasi Manusia Republik Indonesia - Ni Luh Putu Manik Suryani; I Nyoman Putu Budiartha; Putu Ayu Sriasih Wesna (Jurnal Analogi Hukum, 2024)
A will or testament is a document that records a person's wishes regarding what they want to happen after death, and the document can be revoked by the maker in accordance with the provisions of Article 875 of the Civil Code. As a notary, his/her duty is to create an official document that has greater legal force than a document created without the signature of an authorized party. In creating a testament deed, a notary has specific responsibilities related to reporting the will as stipulated in Article 16 paragraph (1) letters i and j of UUJN-P. However, if a notary does not register a deed of testament, the consequence is the downgrading of the document's status to an underhand deed. This could potentially lead to the invalidation or invalidity of the document as evidence made by the notary. This research uses a normative method with a statutory approach and concludes that the non-registration and online reporting of a deed of testament to the Central Register of Testaments by a notary can result in the downgrading of its status to an underhand deed, threatening the validity of the document created by the notary.